New Species and New Records of Caddisflies (Insecta: Trichoptera) from India - Kaur, Simarjit; Garima, Deepti; Pandher, Manpreet Singh (Zootaxa, 2020)
Chimarra gangtokensis sp. nov. is added as a new species from Sikkim. With this addition of a new species, the genus is represented in India by 53 species. Furthermore, Polyplectropus admin Malicky & Chantaramongkol 1993, Hydropsyche briareus Malicky & Chantaramongkol 2000, Cheumatopsyche globosa (Ulmer 1910), and Cheumatopsyche chryseis Malicky & Chantaramongkol 1997 are reported for the first time from India. Also, Chimarra kailishchandrai Malicky 1997a, Cheumatopsyche bhatrapura Malicky 1979, and Oecetis asmada Malicky 1979 are reported for the first time from North Andaman Island, India.